Cost-effectiveness of diagnostic tools and strategies for the screening and diagnosis of tuberculosis disease and infection: a scoping review - Colin A Russell; Morten Ruhwald; Brooke E Nichols; Shaukat Khan; Tom Ockhuisen; Alexandra de Nooy; Helen E Jenkins; Alvin Han; Sarah Girdwood; Mikashmi Kohli (BMJ Public Health)
The objective of this scoping review is to understand the cost-effectiveness of current and future tools/strategies for screening and diagnosis of tuberculosis (TB) infection and disease. To this end, PubMed, EMBASE and SCOPUS were used to identify any English language reports on the cost-effectiveness of TB infection/disease screening/diagnostic strategies published between 1 January 2017 and 7 October 2023. Studies included high-burden/risk TB populations, compared diagnostic/screening methods and conducted a cost-effectiveness/economic evaluation. We stratified the included articles in four groups (cost-effectiveness of diagnosing TB disease/infection and cost-effectiveness of screening for TB disease/infection). A full-text review was conducted, and relevant costing data extracted. Of the 2417 articles identified in the initial search, 112 duplicates were removed, and 2305 articles were screened for title and abstract. 23 full articles were reviewed, and 17 fulfilled all inclusion criteria. While sputum smear microscopy (SSM) has been the primary method of diagnosing TB disease in high-burden countries, the current body of literature suggests that SSM is likely to be the least cost-effective tool for the diagnosis of TB disease. Further scale-up with molecular diagnostics, such as GeneXpert and Truenat, was shown to be broadly cost-effective, with a multitest approach likely to be cost-effective for both screening and diagnosis. There is an urgent need to increase access and remove barriers to implementation of diagnostics that have been repeatedly shown to be cost-effective, as well as to develop new diagnostic and screening technologies/strategies to address current barriers to scale-up.